Classic and Revisionist Sociocultural Theory, and their analyses of expressive language: An empirical and theoretical assessment. (17th March 2015) - Ratner, Carl
Abstract : This article articulates two approaches to sociocultural theory, Vygotsky's classic approach and a contemporary revisionist approach. We examine: (1) their principle tenets for understanding psychology in relation to culture; (2) how they characterize and explain language in particular; and (3) how they characterize and explain a sample linguistic specimen of two dialogues from a middle-class child and a lower-class child. I utilize a critical discourse analysis of the dialogues to empirically determine: (1) which of the two approaches better accounts for the discursive differences; (2) which is a more adequate linguistic theory; (3) which is a more adequate approach to SCT; and (4) which is a more viable and progressive social and political philosophy. We find Vygotsky's classic formulation superior on all counts. This article concerns the politics of language, linguistics, and social theory.